PENANAMAN BIBIT POHON KETAPANG (Terminalia catappa) SEBAGAI UPAYA MENCEGAH BAHAYA EROSI, MENJAGA KETERSEDIAAN AIR TANAH DAN SUMBER PAKAN HIJAUAN TERNAK KAMBING DI DESA PERNEK, KECAMATAN MOYO HULU - Azis, Abdul; Fitriana, Maya; Husni (Jurnal Abdi Insani, 2024)
The impact of drought during the dry season was felt by the people of Pernek Village, Sumbawa Regency, namely that groundwater discharge was reduced significantly. This condition will continue to be a cause for concern as community activities expand corn farming areas to the point of destroying forest vegetation that is difficult to control. High community access to the Batulanteh KPH forest and weak law enforcement are factors in deforestation on Sumbawa Island. Therefore, concrete steps are needed to bridge these two problems. The aim of implementing this service is to educate the community to plant ecological ketapang trees so that they are beneficial economically and economically. Determine the planting point for ketapang trees so that they can function to prevent the danger of soil erosion. The service was used in the form of a lecture on the importance of planting trees by gathering residents, village officials and representatives from the university at the Pernek village hall, then continued with tree planting and assistance during the planting (maintenance) period at predetermined points. The results of this community service activity are increasing public understanding and awareness of climate change by showing enthusiasm in participating in this series of community service activities. Based on the results of the survey before this service program was held, the community did not understand the impact of drought in the form of reduced groundwater discharge due to deforestation due to the large area of ​​corn farming. The community does not yet understand the importance and function of standing trees (including ketapang trees) in reducing the danger of soil erosion during the rainy season. On the other hand, the public can gain new knowledge about the economic potential of the ketapang tree, both in terms of fruit, leaves and wood. This service program has a positive impact on residents regarding the benefits of greening and environmental sustainability.